Pengembangan Media Pembelajaran 3D Berbasis Microsoft Powerpoint Materi the Earth and Beyond Kelas V - Purba, Hengky Tantri Badakara; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (FONDATIA, 2023)
This research aims to develop relevant innovations in the form of 3D Learning Media on The Earth and Beyond material that are appropriate, effective, and get good responses from students for use in class V SDS Adicita Mulia Pontianak. This study uses the ADDIE development model which includes 5 steps, namely: Analysis, Design, Development, Implementation, Evaluation with a mixed method approach. The test subjects in this study were V grade students at the Adicita Mulia Pontianak Private Elementary School, with a total of 23 students. The results of the Research on the Development of 3D Learning Media are categorized as "Very Eligible" for use in learning activities. This can be seen from the results of product validation by the media expert validator with a value of 86%, as well as the material expert validator with a value of 93.18% and the students' responses to the learning media developed "Very Good" seen from the results of the student response questionnaire "83.59 % "The developed learning media is also considered "effective enough" to be used in learning. This can be seen from the results of measuring the effectiveness of media use with a value of "59.70%". So it can be concluded that Microsoft PowerPoint-Based 3D Learning Media is very feasible to develop and use in learning activities.